Penerapan Algoritma C4.5 Untuk Memprediksi Nilai Kelulusan Siswa Sekolah Menengah Berdasarkan Faktor Eksternal - Rizky Haqmanullah Pambudi; Budi Darma Setiawan; Indriati Indriati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Education in the life of a country plays a very important role to ensure the survival of the state and nation. Statistics show that Portugal's education level is at the bottom of the list due to many students dropping out of school. External factors affect the failure of students in completing the field of study, especially the field of study of mathematics. Algorithm C4.5 is one method of data mining to predict students' ability in completing the field of study seen from the external factors of students. The C4.5 algorithm is used to find out the accuracy of the prediction ability of high school students. The feature selection parameters are the factors that affect the ability of high school students in the field of mathematics studies. Testing and analysis results show that the Decision Tree C4.5 algorithm is accurately applied to predict the final grade of high school students with a 60% accuracy rate.